PENGARUH KOMPENSASI TERHADAP LOYALITAS KERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. ASTRA INTERNASIONAL TBK. (TOYOTA AUTO 2000) CABANG BATURAJA - Muhariah, Novie Al; Dahia, Dahlia; Gustia, Ade Rosmeliawati (STIE DWI SAKTI BATURAJA, 2024)
The purpose of this research was to determine the influence of compensation on employees’ job loyaltythrough job satisfaction as an intervening variable at PT. Astra Internasional Tbk. (Toyota Auto 2000)Baturaja branch. This research was a quantitative research. The population in this research was employeesof PT. Astra Internasional Tbk. (Toyota Auto 2000) Baturaja branch with 49 respondents. The analysismethod used was path analysis. The results of the research partially showed that the compensation variable(X) had an influence on employees’ job loyalty (Y), job satisfaction variable (Z) had an influence onemployees’ job loyalty (Y), compensation variable (X) had an influence on job satisfaction (Z), and indirectlyjob satisfaction (Z) intervened between the compensation variable (X) to the employees’ job loyalty variable(Y)